FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KONSERVATISME AKUNTANSI STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2013-2015 - Linda Sulastyowati, 12.05.52.0095; Puspitasari, Elen (Students Journal of Accounting and Banking, 2017)
This study aims to determine the effect of debt covenants, political cost, managerial ownership, institutional ownership and public ownership of the conservatism of accounting in the financial statements of companies manufacturing in Indonesia. This study uses secondary data obtained from the financial statements www.idx.co.id. The population in this study is a company registered in Indonesia Stock Exchange in 2013-2015 with a sample of manufacturing firms. The sampling technique was conducted using purposive sampling. Data were analyzed using multiple linear regression analysis. The results of hypothesis testing can be concluded that the Debt Covenant and no significant negative effect on accounting conservatism. Political cost and no significant negative effect on accounting conservatism. Managerial ownership and significant negative effect on accounting conservatism. Institutional ownership has a significant negative effect on accounting conservatism. Public ownership and significant negative effect on accounting conservatismKeywords:Â Debt Covenants, Political Cost, Managerial Ownership, Institutional Ownership, Public Ownership and Accounting Conservatism